The heterogeneous effects of CSR dimensions on financial performance – a new approach for CSR measurement - Su, Rongjia; Liu, Chunping; Teng, Weili (Journal of Business Economics and Management, 2020)
This paper investigates the differential effects of corporate social responsibility (CSR) dimensions on corporate financial performance (CFP) across sectors in China. This research uses a unique data set provided by China Stock Market and Accounting Research (CSMAR), showing expenditure on CSR programs from 568 Chinese publicly traded firm-year observations from 2008 to 2017. Compared to previous studies using scores produced by extra-financial rating agencies, this research quantifies CSR efforts by corporate expenditure on CSR practices, which offers quantitative and precise information in explaining the CSR-CFP link. The results show that the dimension of the environment has negative effects on financial performance in capital-intensive manufacturing industries. The impact of HR expenditure on CFP is negative in the tertiary sector and resourceintensive manufacturing industries. However, CSR investments in the community are positively related to financial performance in resource-intensive industries and other secondary sector (mining, construction, and utilities). Firms, in general, could gain benefits when spending more on business and financial stakeholders.